CSR reporting levels and financial quality: comparative analysis in indonesian sharia and conventional banking - Nurrahmawati, An; Rahmawati, Wulan; Perwitasari, Dian; Kurniawati, Estetika Mutiaranisa (FORUM EKONOMI, 2021)
The variables tested and analyzed in this study are social responsibility disclosure, earnings quality, profitability, leverage, loss occurrence, and banking characteristics in Indonesia. More specifically, this study compares these variables to Islamic banks and conventional banks. This is done to reveal some various significant effects of religiosity norms that exist in the sharia principles of Islamic banking and do not exist in conventional banking. Measurement of the level of CSR disclosure is carried out using a dichotomous content analysis procedure which is prepared based on the GRI G4 standard. The finding show that conventional bank in Indonesia has a higher level of CSR disclosure than the islamic bank, but its not significantly different from the statistic test. Further descriptive analysis regarding the different characteristics of these two entities have been done to find the reasons for this finding. Subsequent findings show that the significant age gap of these banks affects the stability of the bank and their level of management ability. The characteristic of the conventional banks are older in age, larger in asset size, and their awareness of using better quality auditors are better. Even so, Islamic banks have a better level of earnings quality, lower losses, and a lower level of leverage.